Multiprofessional instrument for tracheal decannulation in adults: content validity - Coltro, Paulo Henrique (2022)
Introduction: Tracheal decannulation needs multiprofessional evaluation observing success predictor criteria. A validated instrument can increase the safety of the procedure, reduce the length of stay and ensure better quality of life. Objective: To develop and perform the content validity of a multiprofessional instrument for tracheal decannulation in adults. Method: Cross-sectional descriptive study, with 24 judges: doctors, physiotherapists, speech therapists and nurses. The instrument was developed and presented through an electronic form where the judges took their notes. The Content Validity Index by item (CVI-I) and total (CVI-T) were calculated to verify evidence of validation. In unverified items, adjustments were made pointed out by the judges and submitted to the new evaluation phase in order to obtain complete validation of the instrument. Results: First evaluation phase, the items: Identification, Ventilatory History, Vital Signs, Consciousness/Collaboration, Ventilatory Data, Opinion and Legend obtained CVI-I > 0.78, were considered validity. The items Muscular Performance and Speech and Swallowing did not obtain adequate validity CVI-I 0.67 and 0.17, respectively. Therefore, they were submitted to the second phase of evaluation. In this phase, these items were validated obtaining CVI-I=0.83 in the item Muscular Performance and CVI-I=1.0 in the item Speech and Swallowing. From the mean of CVI-I, the value CVI-T=0.9 was obtained, validity all the instrument. Conclusion: Multiprofessional instrument that can help in the process of tracheal decannulation in adults was developed and validity in content post two phases of evaluation by a group of expert judges in the area.